Gender-based constraints and opportunities to agricultural intensification in Ethiopia: A systematic review - Mulema, Annet A.; Damtew, Elias (International Livestock Research Institute, 2016)
We employ a community capital’s framework to provide a holistic perspective of the stock and interaction between the capitals required by men and women farmers for effective engagement in agricultural intensification. We reviewed literature which was validated by male and female farmers in four regions of Ethiopia. Ethiopia has relatively equitable land distribution due to the land reform. Although reform has enhanced women’s access to land, participation in decision-making and asset control are yet to be achieved. Female-headed household farm sizes are smaller compared to those of male-headed households. On average men possess more livestock species and numbers than women. Therefore, women have limited access to manure for soil fertility management and adoption of the practice. Time use studies show that women work longer hours compared to men, affecting their decisions to adopt time and labour intensive technologies. Due to cultural norms, there are discrepancies in access to information and extension services. Inadequate access to credit lowers women’s access to farm inputs, such as seeds, tools and fertilizers to invest in irrigation and land improvements. Women have lower membership to farmer-based organizations compared to men, and lesser for women in male-headed households. When women’s membership in informal groups is higher, women can achieve economies of scale in access to markets, build confidence, and leadership. The Ethiopian government has plans to develop the agricultural sector and gender equality is one of the pillar strategies. Policy enforcement, transformation of gender constraining norms, gender capacity development, development of women’s social capital, increasing women’s access to and control over resources and benefits from their investment will minimize the inequalities.